Transformasi Pendidikan di Era Globalisasi: Integrasi dan Tantangan terhadap Sistem Pendidikan Indonesia - Abdul Karim; Usep Saepul Anwar; Suherman Suherman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The main aim of this study is to understand how globalization influences the adaptation of curricula and teaching methods in Indonesia and its impact on broader access to education. The methodology used in this research is a qualitative approach through literature study. Data is collected from various relevant sources. An in-depth literature analysis explored how educational institutions in Indonesia adapt to the demands of globalization and the implications for inclusive and practical education. The research results show that globalization has influenced Indonesia's curriculum and teaching methods, with a significant increase in the use of technology and international collaboration. However, challenges such as cultural homogenization and disparities in access to education remain, especially in remote areas. In the face of this, a more inclusive approach to education policy is needed to ensure that all students, regardless of their geographic and social background, have equal access to quality education. The conclusion is that although globalization brings many benefits to the education system in Indonesia, such as increasing access and quality of education through technology, there is still a lot of work that needs to be done to overcome existing challenges. Keywords: Access to Education, Globalization, Curriculum, Teaching Methods